Generation and management of waste in residental construction / Siti Akhtar Mahayuddin ... [et al.] - Mahayuddin, Siti Akhtar; Periera, Joy Jacqueline; Wan Badaruzzaman, Wan Hamidon; Mokhtar, Mazlin (Universiti Teknologi MARA, Perak, 2011)
Construction waste profile is important to assess the viability of good waste management practices. However, little information is known about the quantity and characteristics of construction waste generated and its management. Lack of understanding, results in improper waste management practice. The generation and characterisation of construction waste have to be identified together with current waste management practice. Therefore, a series of site audit has been carried out in several on-going housing projects in Ipoh, Perak, Malaysia. The calculation of the total construction waste quantity and the floor area constructed gives a generation rate of 16.55 kg/m2. This rate should be disseminated to all parties involved in construction with a view towards widespread use in future construction waste estimation.